Clinical outcomes of low-intensity area without attenuation and cholesterol crystals in non-culprit lesions assessed by optical coherence tomography. (September 2021) - Usui, Eisuke; Matsumura, Mitsuaki; Mintz, Gary S.; Zhou, Zhipeng; Hada, Masahiro; Yamaguchi, Masao; Hoshino, Masahiro; Kanaji, Yoshihisa; Sugiyama, Tomoyo; Murai, Tadashi; Lee, Tetsumin; Yonetsu, Taishi; et al.
Abstract: Background and aims: Pathologists have shown that intraplaque hemorrhage contributes to plaque destabilization and is frequently co-located with cholesterol crystals (CC). Optical coherence tomography (OCT)-detected low-intensity area without attenuation (LIA) may represent intraplaque hemorrhage. We aimed to examine the prevalence and impact of OCT-detected LIA + CC in untreated non-culprit lesions (NCLs) on subsequent major adverse cardiac events (MACE). Methods: OCT imaged NCLs in the culprit vessel in the patients who underwent OCT-guided percutaneous coronary intervention were included. An NCL was a lesion with >90° of diseased arc (≥0.5 mm intimal thickness), length ≥2 mm, and >5 mm away from stent edge. CC was defined as a thin linear region of high intensity. NCL-related MACE includes cardiac death, myocardial infarction, or ischemia-driven revascularization attributed to NCLs. Results: We included 735 NCLs in 566 patients with 2.5 ± 0.7 years follow-up. The prevalence of concomitant LIA with CC (LIA + CC) was 15.5% (114/735). Three-year NCL-related MACE rate was 2.9% (20 events) at a lesion level and 15.6% (78 events) at a patient level. Untreated NCLs with LIA + CC had an increased risk for NCL-MACE (adjusted hazard ratio [HR] 3.09, 95% confidence interval [CI] 1.27–7.50, p = 0.01) along with thin-cap fibroatheroma (adjusted HR 4.38, 95% CI 1.44–13.30, p < 0.01) and minimum lumen area <3.5 mm 2 (adjusted HR 5.33, 95% CI 1.94–14.62, p < 0.01). Patients having ≥1 untreated NCL with LIA + CC had an increased risk for NCL-MACE (adjusted HR 1.95, 95% CI 1.19–3.19, p < 0.01). Conclusions: An OCT-detected LIA + CC in an NCL was associated with subsequent NCL-MACE. Graphical abstract: Image 1 HIGHLIGHTS: Low-intensity area without attenuation and cholesterol crystal (LIA + CC) often coexist LIA + CC were present in 16% of untreated non-culprit lesions LIA + CC predicts future adverse cardiac event from untreated non-culprit lesions